Морфогенез Cladrastis kentukea (Dum.-Cours.) Rudd в умовах in vitro - Nebykov, M.V.; О.L. Porohnyava, О.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The sterilization of plant material, selection and modification of nutrient mediums and peculiarities of microclonal breeding of the Cladrastis kentukea (Dum.-Cours.) Rudd in vitro were investigated. The dependence of the explants morphogenesis from hormonal composition of nutrient mediums is considered.